Selective controlled base isolation system with magnetorheological dampers. - Ribakov, Y.
A base isolation system composed of low damping isolation bearings and magnetorheological (MR) fluid dampers is described. The MR fluid changes its properties under the influence of a magnetic field resulting in a damper with characteristics that may be modified in real time. This feature enables optimal control under changing excitations in a stable and cost effective manner. The voltage is applied according to a selective control strategy. According to the proposed approach the dampers are activated only within a given range of the base displacements. The selective control improves the efficiency of the system and significantly reduces the control forces required for an optimal structural behaviour. Models of five and eight storey buildings are used to study the efficiency of the proposed system.
Keywords: Magnetorheological dampers; Base isolation system